Cervical Ganglioneuroma in a Four Year Old Boy - Chintalapudi, Deepthi Chandrika; Nerune, Savitri Mallikarjun; Patil, Vijaya L; Arakeri, S U (Annals of Pathology and Laboratory Medicine, 2020)
Ganglioneuroma is a rare benign neurogenic tumour arising from the sympathetic system. Ganglioneuromas are most commonly seen in posterior mediastinum, retroperitoneum, adrenal gland and rarely seen in cervical region. GNs tend to occur in older children at the age of 5 to 7 years. Here, we present a case of cervical ganglioneuroma in a 4 year old male child who presented with slow growing painless lateral neck swelling since birth.